Analisis dan Perancangan Sistem Antrian Pembayaran Pajak Daerah Kabupaten Jayapura - Fernando Firdaus Mansyur; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Badan Pengelola Pendapatan Daerah (BAPPENDA) is a government agency engaged in regional taxation. Badan Pengelola Pendapatan Daerah (BAPPENDA) has several functions, one of which is the payment of taxes. Where in this function problems often occur during the queuing process carried out by taxpayers. The accumulation of queues resulted in unclear bookkeeping processes carried out by tax counter employees. On the side of taxpayers, they can experience inconvenience when queuing. Therefore, Badan Pengelola Pendapatan Daerah (BAPPENDA) needs a queuing information system that can make it easier for taxpayers and counter officers to make tax payments. In conducting the requested system design, researchers use the Object Oriented Analysis and Design (OOAD) method. In the analysis process, the system requirements data were collected from respondents. In this process, several system requirements are obtained, namely this system has 3 actors, 9 features, 9 functional requirements, and 2 non-functional requirements. Obtained several needs such as use case diagrams, activity diagrams, sequence diagrams, and class diagrams. After the analysis and design phase is complete, an evaluation process is carried out using the Traceability Matrix and Usability evaluation. At the traceability evaluation stage, very satisfying results were obtained, namely all needs were met in the design diagrams. And the results of the Usability evaluation, the efficiency aspect as a counter employee gets 96.1% and a taxpayer of 100%. In terms of the effectiveness aspect, counter employees earn 0.99% and taxpayers 0.1%.